Pengaruh Paparan Radiasi Telepon Genggam Terhadap Aktivitas Enzim Katalase Kelenjar Parotis Rattus norvegicus Strain Wistar - Yoannita; Isidora Karsini; Syamsulina Revianti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Handheld mobile phones have become a cultural accessory device. Nevertheless, the use mobile phones has given rise to great concern because of possible adverse health effects from exposure to the radiofrequency radiation (RFR) emitted by the device. There have been plenty of researches reportedly establishing the damaging effect of radiofrequency radiation emitted from cell phone on the biological tissues in the body, but only several researches report the effect of handheld mobile phone radiation in oral cavity.Purpose: The aim of this experiment was to examine the difference effect of rat parotid gland catalase activity cause by low and high radiation handheld mobile phone. Material and Methods: This study was true experimental study with post test only control group design. 72male Wistar rats, 3 months old, with body weight 200 grams were used in this experiment, devided into 3 major group. Group 1 was negative contol group, group 2 was radiated by handheld mobile phone with low radiation, and group 3 was radiated by handheld mobile phone with high radiation 1 hour per day until 7 days, 14 days, and 21 days. Parotid gland catalase activity was measured by spectrophotometer λ 240. Data were analyzed by KruskallWallis and Mann-Withney test. Result: Low radiation handheld mobile phone was not altered catalase activity until 7, 14 and 21 days. High radiation handheld mobile phone was not altered catalase activity until 7and 14, but catalase activity was significantly increase at 21 days. Conclusion: Radiation emitted from the high radiadion handheld mobile phone until 21days was able to rise rat parotid gland catalase activity .